Ammonia Volatilization and Phosphate Release from Compacted Mixed Fertilizers in Pure System and in an Acid Soil - Kasim, Susilawati (2003)
Urea and phosphate rock (PR) have been widely used in Malaysian agriculture. However, ammonia (NH3) volatilization and slow release of P are two major problems encountered when urea and PR fertilizers were used. High pH, AI and Fe oxides content and low cation exchange capacity (CEC) have been identified as causing these problems in soil. Peat and triple superphosphate (TSP) may be mixed to supply humic substances from peat to reduce P fixation, N loss and proton (H+) from TSP to solubilize PR in water and soil. Thus, a study was initiated to investigate the effect of these mixed fertilizers on NH3 volatilization and dissolution of PR in a pure system and in an acid soil. Various combinations of urea, TSP, CIPR fertilizers and peat were compacted and studied in the two systems in the laboratory. In pure system, the N loss following addition of peat (5.09%) is better than TSP (28.15%). Four combinations of fertilizers gave the second highest P dissolution (70.53%) at day one and day 10 (71.15%) based on changes in P released (L\P) method after urea plus TSP and peat. Almost 40% of changes in Ca released (b.Ca) was detected in solution when any combination of TSP and Christmas Island Phosphate Rock (CIPR) was used in the mixture after 10 days. This is due to the production of phosphoric acid by TSP. Surface application of compacted mixed fertilizer on the soil showed that urea plus TSP and CIPR and urea plus TSP and peat managed to decrease the loss of N by nearly 50% compared to only urea. This is due to the production of Ca2+ by P sources and additional CEC by peat. Delay in the peak N loss differed with fertilizer combinations: urea + TSP +CIPR (3 days), urea + TSP + CIPR + peat (7 days), urea + TSP + peat (7 days) and urea + peat (5 days). The CIPR and peat mixture showed the highest L\P value (394.66 mg kg-1) after 90 days of incubation in soil. On average, the highest (310.98 mg kg-1) P dissolution as measured by b.P method was obtained using urea plus TSP, CIPR and peat. This was attributed to the protons supplied by TSP and Casink from peat which promoted the dissolution of PR in mixed fertilizer. Thus, compacted mixed fertilizer is an effective way to decrease NH3 volatilization and increase L\P in soil and pure system. However, this depends on the combination of the fertilizers used.